Genomic Analysis of a Highly Virulent NDM-1-Producing Escherichia coli ST162 Infecting a Pygmy Sperm Whale (Kogia breviceps) in South America - Sellera, Fábio P.; Cardoso, Brenda; Fuentes-Castillo, Danny; Esposito, Fernanda; Sano, Elder; Fontana, Herrison; Fuga, Bruna; Goldberg, Daphne W.; Seabra, Lourdes A. V.; Antonelli, Marzia; Sandri, Sandro; Kolesnikovas, Cristiane K. M.; et al. (Frontiers in Microbiology, 2022)
Carbapenemase-producing Enterobacterales are rapidly spreading and adapting to different environments beyond hospital settings. During COVID-19 lockdown, a carbapenem-resistant NDM-1-positive Escherichia coli isolate (BA01 strain) was recovered from a pygmy sperm whale (Kogia breviceps), which was found stranded on the southern coast of Brazil. BA01 strain belonged to the global sequence type (ST) 162 and carried the blaNDM-1, besides other medically important antimicrobial resistance genes. Additionally, genes associated with resistance to heavy metals, biocides, and glyphosate were also detected. Halophilic behaviour (tolerance to > 10 % NaCl) of BA01 strain was confirmed by tolerance tests of NaCl minimal inhibitory concentration, whereas halotolerance associated genes katE and nhaA, which encodes for catalase and Na+/H+ antiporter cytoplasmic membrane, respectively, were in silico confirmed. Phylogenomics clustered BA01 with poultry- and human-associated ST162 lineages circulating in European and Asian countries. Important virulence genes, including the astA (a gene encoding an enterotoxin associated with human and animal infections) were detected, whereas in vivo experiments using the Galleria mellonella infection model confirmed the virulent behaviour of the BA01 strain. WHO critical priority carbapenemase-producing pathogens in coastal water are an emerging threat that deserves the urgent need to assess the role of the aquatic environment in its global epidemiology.